A comparison between allogeneic stem cell transplantation from unmanipulated haploidentical and unrelated donors in acute leukemia. Issue 1 (December 2017) - Piemontese, Simona; Ciceri, F.; Labopin, M.; Arcese, W.; Kyrcz-Krzemien, S.; Santarone, S.; Huang, H.; Beelen, D.; Gorin, N.; Craddock, C.; Gulbas, Z.; Bacigalupo, A.; et al.
Abstract Background In the absence of a HLA-matched related or matched unrelated donor, allogeneic stem cell transplantation (allo-SCT) from mismatched unrelated donors or haploidentical donors are potential alternatives for patients with acute leukemia with an indication to allo-SCT. The objective of this study was to compare the outcome of allo-SCT from T cell-replete haploidentical (Haplo) versus matched (MUD 10/10) or mismatched unrelated donor at a single HLA-locus (MMUD 9/10) for patients with acute leukemia in remission. Methods Two hundred sixty-five adult patients with de novo acute leukemia in first or second remission that received a Haplo-SCT between January 2007 and December 2013 were compared with 2490 patients receiving a MUD 10/10 and 813 receiving a MMUD 9/10. Propensity score weighted analysis was conducted in order to control for disease risk imbalances between the groups. Results The weighted 3-year non-relapse mortality and relapse incidence were 29 and 30% for Haplo, 21 and 29% for MUD 10/10, and 29 and 25% for MMUD 9/10, respectively. The weighted 3-year leukemia-free survival (LFS) and overall survival (OS) were 41 and 46% for Haplo, 50 and 56% for MUD 10/10, and 46 and 48% for MMUD 9/10, respectively. Using weighted Cox model, both LFS and OS were significantly higher in transplants from MUD 10/10 compared from those in Haplo but not different between transplants from MMUD 9/10 and Haplo. The type of donor was not significantly associated with neither acute nor chronic graft-versus-host disease. Conclusions Patients with acute leukemia in remission have better outcomes if transplanted from a MUD 10/10. We did not find any significant difference in outcome between transplants from MMUD 9/10 and Haplo, suggesting that both can be equally used in the absence of a 10/10 MUD. Key point 1 Better outcomes using fully (10/10) matched unrelated donor for allo-SCT in acute leukemia in remission. Key point 2 Similar outcomes after allo-SCT from unmanipulated haploidentical graft or mismatched (9/10) unrelated donor in acute leukemia in remission.